2020
DOI: 10.31557/apjcp.2020.21.4.1097
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Blood Vessels Profile in Oral Carcinogenesis: An Immunohistochemistry Study

Abstract: Angiogenesis is the emergence of new blood vessels from pre-existing capillaries. It is an essential step in tumor growth and metastasis because the new blood vessels provide oxygen and nutrition to the cells that are proliferating and facilitate the drainage of metabolites, in addition to functioning as a means of transportation for tumor cells (Souza et al., 2007). According to Folkman, cancer begins as avascular nodules (Folkman, 1971) and is only able to grow beyond 2 millimeters in three

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In HNSCC and PMDs, mast cells follow a general trend similar to other immune cells in the majority of studies—a gradual increase from normal to dysplasia to cancer—and are generally associated with microvessels [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. However, even this basic analysis of mast cells produced different results in other groups [ 103 , 104 , 105 , 106 ]. The reason for the differences in these studies is unclear.…”
Section: Mast Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…In HNSCC and PMDs, mast cells follow a general trend similar to other immune cells in the majority of studies—a gradual increase from normal to dysplasia to cancer—and are generally associated with microvessels [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. However, even this basic analysis of mast cells produced different results in other groups [ 103 , 104 , 105 , 106 ]. The reason for the differences in these studies is unclear.…”
Section: Mast Cellsmentioning
confidence: 98%
“…The reason for the differences in these studies is unclear. Few studies used anti-tryptase antibodies to determine mast cell identity and these studies could not detect an increase in mast cells in cancer tissues (e.g., Teófilo [ 106 ]).…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was considered to be positive nuclear reaction for Ki-67 by expression of brownish staining restricted to the nucleus (22) . Large and small vessels that were CD31-positive reaction (blood vessels) had developed and were concentrated at the submucosa and lamina propria of the lingual mucosa (23) .…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…It has been shown that more blood vessels and MCs are found in the environment of OSCC compared to healthy oral mucosa, supporting the hypothesis that MCs have a tumor-promoting effect in OSCC by inducing angiogenesis [ 10 ]. In contrast, MC density has recently been shown to decrease from oral potentially malignant disorders (OPMD) to OSCC [ 11 ], and increased vascularity in OSCC appears to be inversely related to MC density [ 12 , 13 ]. These findings suggest a protective role of MCs in OSCC.…”
Section: Introductionmentioning
confidence: 99%